Deletion of the Infectious spleen and kidney necrosis virus ORF069L reduces virulence to mandarin fish Siniperca chuatsi. Issue 95 (December 2019) - Lin, Yi-Fan; He, Jian; Zeng, Ruo-Yun; Li, Zhi-Min; Luo, Zhi-Yong; Pan, Wei-Qiang; Weng, Shao-Ping; Guo, Chang-Jun; He, Jian-Guo
Abstract: Mandarin fish ( Siniperca chuatsi ) is a significant cultured species with high added value in China. With the expansion of farming, diseases of mandarin fish such as Infectious spleen and kidney necrosis virus (ISKNV) diseases are becoming more and more serious. Human endogenous retrovirus subfamily H long terminal repeat associating protein 2 (HHLA2) is a type 1 transmembrane molecule with three extracellular Ig domains (IgV-IgC-IgV) and plays important roles in the T cell proliferation and tumorigenesis. The HHLA2-homologues have not been found in virus. In this study, a viral HHLA2 protein encoded by ISKNV ORF069L was identified and the virulence of the deleted ORF069L reconstruction ISKNV strain (Δ ORF069L ) was investigated. ISKNV ORF069L gene was predicted to encode a 222-amino acids peptide. The bioinformation analysis revealed that ISKNV ORF069L contained an Ig HHLA2 domain and was homologous to vertebrate B7-CD28 family proteins. The recombinant virus strain of Δ ORF069L was constructed by homologous recombination technology. The virus titer and growth curves between ISKNV wild type (WT) and Δ ORF069L on cellular level showed no significant differences indicating that the ORF069L did not influence the ISKNV replication. The expression levels of immune-related genes ( Mx1, IL-1β, IL-8, TNF-a and IgM ) were increased in fish infected with Δ ORF069L, compared to those in fish infected with ISKNV WT. Furthermore, the lethality caused by Δ ORF069L declined by 40% compared with ISKNV WT, indicating that ORF069L was a virulence gene of ISKNV. Most importantly, the protection rate was nearly 100% for fish immunized with Δ ORF069L strain. Those results suggested that Δ ORF069L could be developed as a potential attenuated vaccine against ISKNV. Our work will be beneficial to promote the development of gene deletion attenuated vaccines for ISKNV disease. Highlights: A viral HHLA2 protein encoded by ISKNV ORF069L was identified. A recombinant virus of ISKNV ORF069L deletion (Δ ORF069L ) was constructed. ISKNV ORF069L was an important virulence gene. The protection rate was nearly 100% for fish immunized with Δ ORF069L strain. Δ ORF069L could be developed as an attenuated vaccine against ISKNV.